Effect of platelet-rich plasma on bone healing of fresh frozen bone allograft in mandibular defects: a histomorphometric study in dogs - Messora, Michel R.; Nagata, Maria José Hitomi [UNESP]; Pola, Natalia M. [UNESP]; Campos, Natalia de [UNESP]; Fucini, Stephen E. [UNESP]; Furlaneto, Flavia A. C. (Wiley-Blackwell, 2013)
Objective: This study histologically analyzed the healing of fresh frozen bone allograft (FFBA) with or without platelet-rich plasma (PRP) in bony defects surgically created in the mandible of dogs.Material and methodsBilateral resection defects were surgically created on the inferior border of the mandible in 10 dogs. The defects were randomly divided into three groups: C (the defect was filled by blood clot only), FFBA (the defect was filled with particulate FFBA), and FFBA/PRP (the defect was filled with particulate FFBA combined with PRP). The animals were euthanized at 12weeks post-surgery. Histomorphometric and histological analyses were performed. Data were statistically analyzed using Friedman test and Dunn test (P<0.05).ResultsGroup FFBA/PRP presented a statistically greater mineralized bone area and a smaller marrow bone area than Groups FFBA and C.ConclusionsThe use of PRP improved the incorporation of FFBA, increasing the density of newly formed bone at 12weeks post-surgery.
Keywords: bone regeneration; transplantation; homologous; platelet-rich plasma